Ultrafast Electron Transfer in Low‐Band Gap Polymer/PbS Nanocrystalline Blend Films. (7th December 2015) - Guo, Wenping; Yuan, Jianyu; Yuan, Haochen; Jin, Feng; Han, Lu; Sheng, Chuanxiang; Ma, Wanli; Zhao, Haibin
Abstract : Ultrafast charge transfer dynamics in hybrid blend films of a low band‐gap polymer poly(2, 6‐( N ‐(1‐octylnonyl)dithieno[3, 2‐b:20, 30‐d]pyrrole)‐alt‐4, 7‐(2, 1, 3‐benzothiadiazole)) (PDBT) and PbS quantum dots (QDs) are studied by using ultrafast transient transmission spectroscopy. It is observed that the transient bleaching signal arising from excitons of the PDBT displays a much faster recovery, within the time delay of ≈5 ps, in hybrid films than in the neat PDBT film. In contrast, the bleaching signal resulting from the electron filling of the QDs in hybrid films shows an extra rising component during ≈1–5 ps, which is absent in the pristine QDs. These results indicate the ultrafast electron transfer from the lowest unoccupied molecular orbital energy level of the PDBT to the conduction band of the QDs in the time scale of several ps after laser excitation. A transient absorption signal within 1 ps in the hybrid films is also found, indicating the emergence of charge transfer states (CTs). The CTs formed at the interface of the hybrid blend may facilitate the charge separation and transfer. It is estimated that over 80% of the photoexcited electrons in the PDBT may be transferred into the QDs. The transfer efficiencies show a positive correlation with the power conversion efficiencies of the corresponding hybrid solar cells. Abstract : Efficient electron transfer with the time scale of picoseconds in polymer/PbS quantumdot (QD) hybrid films under photoexcitation is observed. The transfer efficiencies show close correlations with the morphology of the hybrid films and the power conversion efficiencies of the solar cells. The appearance of interfacial charge transfer states may facilitate the charge separation for promoting solar cell performance.